Aerobic Power and Capacity in Highly Trained National-Level Youth Soccer Players Through On-Field Gas Exchange Assessment in an Ecological Context: A Brief Report - Martin Fernando Bruzzese; Gastón César García; Carlos Rodolfo Arcuri; Mauro Darío Santander; Jeremías David Secchi; José Augusto Rodrigues dos Santos; Rodrigo Zacca (Physiologia, 2025)
Background: Extensive data exists on external load during training and competition, but a significant gap remains in understanding internal physiological load, particularly in protocols conducted in ecological settings. Given the scarcity of studies on the on-field cardiorespiratory profiles of national-level athletes, especially in Argentine soccer, this study aimed to identify the on-field cardiorespiratory fitness profile of ten highly trained youth field soccer players (13.6 ± 1.3 years old) from both the first league of the Argentine Football Association and members of the national team in their age group category in the current year. Methods: Each athlete performed an on-field cardiorespiratory exercise test (20-m Shuttle Run Test, 20-m SRT) with the COSMED K5 wearable metabolic system (COSMED, Rome, Italy) in dynamic micro-mixing chamber mode. The 20-m Shuttle Run Test involves running back and forth between two lines set 20 m apart, following the pace set by an audio signal. The test starts at a running velocity of 8.5 km·h−1 and increases by 0.5 km·h−1 each min. Results: Mean velocity at maximal oxygen uptake (v<semantics><mover accent="true">V˙</mover></semantics>O2max) was 12.3 ± 0.7 km·h−1. The maximal oxygen uptake (<semantics><mover accent="true">V˙</mover></semantics>O2max) on-field was 67.1 ± 5.3 mL·kg−1·min−1. The <semantics><mover accent="true">V˙</mover></semantics>O2 at the first and second ventilatory thresholds (VT1 and VT2) were identified at 67.0 ± 3.0% <semantics><mover accent="true">V˙</mover></semantics>O2max (44.9 ± 3.3 mL·kg−1·min−1) and 84.7 ± 3.7% <semantics><mover accent="true">V˙</mover></semantics>O2max (56.8 ± 3.8 mL·kg−1·min−1), respectively. Conclusions: This is a scarce on-field gas exchange assessment, conducted in an ecological context using a portable analyzer with highly trained national-level youth soccer players from the Argentine youth national team, which underlines their cardiorespiratory fitness, showcases their high-performance potential, offers valuable insights into a selective group of players, and provides a reference for larger-scale research on elite youth soccer and the long-term development of aerobic power and capacity.